Using Toongue Twister Technique to Improve Students' Pronunciation Ability - Nur Trisna Juniarti; Amzah; Magdahalena (Inspiring: English Education Journal, 2020)
This study was aimed to see the Improving Pronunciation Ability at the first-grade students of SMK Negeri 2 Parepare. The objective of this research is to get the empirical data of the differences between students’ scores on pronunciation tests who were taught by using tongue twister technique and the students who were not taught by using tongue twister technique. The population of this research consists of 69 students and the sample of the research X Listrik A as the experimental class consists of 35 students. The research method used in this research was a quantitative method using a quasi-experimental design (nonequivalent control group). The data was collected through pretest and posttest. It aimed to know whether the tongue twister technique in teaching pronunciation can improve students’ pronunciation ability. Based on the calculation, the result of the data analysis by using t-test showed the value of t-test (to) was higher than t-table (tt), to >tt = 3.0 > 1.667, insignificant degree of 0.05 (5%). As the statistical hypotheses show, if ttest (to) >ttable (tt) insignificant degree of 0.05 (5%), it means that the tongue twister technique (Ha) is accepted and the Null Hypothesis (Ho) is rejected. In conclusion, tongue twister technique is able use in teaching pronunciation.